Optimization of Welfare State Policy for the Development of Halal Industry in the Framework of Sharia Economy - Maarif , Muhamat Nur; Munir , Sirajul; Towpek , Hadenan; Zulqarnain , Iskandar (Suhuf: International Journal of Islamic Studies, 2025)
This study explores the optimization of welfare state policies within the framework of halal industry development that aligns with Sharia economic principles. It aims to analyze the government's role in establishing an ecosystem that fosters the growth of the halal sector while upholding social welfare objectives. The research employs a comparative policy analysis across various countries, a review of Sharia economic literature, and interviews with stakeholders in the halal industry. The findings reveal that integrating Sharia values into the welfare state policy framework can promote innovation and expansion of the halal industry, while simultaneously enhancing overall societal welfare. This study offers policy recommendations to strengthen the synergy between welfare state goals and the advancement of the Sharia economy through the halal sector. The results are intended to guide policymakers in designing sustainable and inclusive development strategies, particularly in Muslim-majority countries where the halal industry and Sharia economy hold significant potential for social and economic progress.